2021
DOI: 10.1186/s40662-021-00227-5
|View full text |Cite
|
Sign up to set email alerts
|

Sirius Scheimpflug–Placido versus ultrasound pachymetry for central corneal thickness: meta-analysis

Abstract: Background To compare the difference in central corneal thickness (CCT) measurements in normal eyes between a rotating Scheimpflug camera combined with a Placido-disk corneal topographer (Sirius, CSO, Italy) and ultrasound pachymetry (USP). Methods A systematic literature search was conducted for relevant studies published on PubMed, Medline, EMBASE, and the Cochrane Library and ClinicalTrials.gov from inception to August 1st, 2019. Primary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Most of these publications compared the results of measurements taken with the present gold standard, ultrasound pachymetry. Jin et al [10] and Jorge et al [22] demonstrated excellent accordance in measurements taken by a Scheimpflug camera with ultrasound pachymetry. Especially Jorge et al [22] underlined that a feasible compensation of the results remained not possible.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Most of these publications compared the results of measurements taken with the present gold standard, ultrasound pachymetry. Jin et al [10] and Jorge et al [22] demonstrated excellent accordance in measurements taken by a Scheimpflug camera with ultrasound pachymetry. Especially Jorge et al [22] underlined that a feasible compensation of the results remained not possible.…”
Section: Discussionmentioning
confidence: 81%
“…Most studies compared the results with the gold standard, ultrasound pachymetry. Various authors have found excellent correlations of CCT measured with Scheimpflug diagnostics and ultrasound pachymetry [10,12,22,25,38,42] . Similar results were found for OCT [12,15,29,34] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It seems more that 280-300µm is more common nowadays. 36 275µm ist „just“ +10% above 250µm as a safety margin, the 25µm extra safety margin can be understood as a reserve for potential undercorrections of up to ∼1.5D; but at the same time is ∼50% (half the thickness) of the average normal central corneal pachymetry; 37 finally, since the introduction of percentage tissue altered (PTA), a PTA of ∼40% has been proposed as the cutoff value for enhanced ectasia risk, 38 considering 480µm (according to the german “Kommission Refraktive Chirurgie der DOG und des BVA”) 39 as the minimum pachymetry suitable for lamellar refractive surgery (whether LASIK or lenticule extraction); an RST of 275µm would represent a 42.7% PTA.…”
Section: Discussionmentioning
confidence: 99%
“…Patients underwent corneal topography with bon Sirius corneal topographer and tomographer (CSO, Italy) which combines placido disk topography with Scheimpflug tomography of the anterior segment (Jin et al, 2021). The CCT was recorded, the ICA was measured in all the quadrants and the average in both eyes was recorded.…”
Section: Methodsmentioning
confidence: 99%